JOB ANALYSIS FOR PERSONS WITH DISABILITIES IN STATE CIVIL APPARATUS NEEDS PLANNING - Arif Budiman; Lina Miftahul Jannah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
As a form of respect and fulfillment of the rights of persons with disabilities in working, the Government issued an affirmation policy by opening the formation of persons with disabilities as the Aparatur Sipil Negara-ASN (State Civil Apparatus). In the implementation of ASN recruitment, there are several problems faced, including the formation of persons with disabilities that are not filled and requirements that have not accommodated the interests of persons with disabilities. One problem is the non-fulfillment of the formation, or the tan caused by the job analysis. This study aims to describe the process of job analysis for persons with disabilities in the recruitment and selection of ASN with a type of narrative descriptive research. Data collection was carried out through interviews with informants from the Ministry of State Apparatus Empowerment and Bureaucratic Reform, the State Civil Service Agency, the Ministry of Social Affairs and Australia Indonesia Disability Research Advocacy Network and document studies by reviewing the literature on job analysis for persons with disabilities and regulations related to job analysis. The results showed that the process of analyzing job analysis of jobs in the context of planning ASN needs as stipulated in the Peraturan Menteri Pemberdayaan Aparatur Negara dan Reformasi Birokrasi Nomor 1 Tahun 2020 concerning Job analysis and Workload Analysis does not specifically regulate for persons with disabilities. The availability of facilities and the lack of a comprehensive understanding of the issue of inclusivity in the fulfillment of the right to work for persons with disabilities are factors in the emergence of job requirements that are not accommodating to all kinds of disabilities. The provision of accessibility and decent accommodation has not been a major concern in the preparation of the ASN job analysis.